“The Tale of Ivan the Fool...” by L.N. Tolstoy (1885–1886): The Problem of Editions - Irina I. Sizova (Studia Litterarum)
The purpose of the article is to reveal the problem of editions in the history of “The Tale of Ivan the Fool...” text by L.N. Tolstoy (1885–1886). The objective of the research is the reading, differentiation and analyzis of this work’s manuscripts saved in the the Manuscript Department of the Leo Tolstoy State Museum in Moscow and in the University of Chicago Library (USA). The scientific novelty lies in the fact that for the first time an integrated approach has been applied to the study of the history of the creation of the “Tale of Ivan the Fool...”, combining textual and literary (poetics, historical, literary and biographical contexts) areas of research. The author of the article comes to the conclusion that the early manuscripts did not have editions radically different from the main text, as it is considered to be a scientific tradition. The results of the research prove that the plot parts, the figurative system, visual and expressive means for the integral expression of the genre form of the idea — a social utopia in the kind of folk tale were consistently formed in the draft materials. The article emphasizes that folklore details (stories about the three brothers, about the victory of man over evil spirits) were the allegorical basis for the artistic presentation of the main theses of Tolstoy’s religious, philosophical and publicistic writings in the 1880s. These theses include the idea of non-resistance to evil by violence, criticism of the military strategy of states, the tax system of societies, the idea of enslaving the weak by the strong with the sword and money, glorification of agricultural labor, the antithesis of mental activity and physical labor in the history of mankind.